Respuesta :

Answer:

6 - 2x = 3 /+2x (on both sides)

6 = 2× + 3 /-3

3 = 2x /:2

1,5=x

-> x = 1,5

you're welcome

Step-by-step explanation:

[tex] \tt{6 - 2x = 3}[/tex]

We want to remove 6 first. Since the original equation is +6 , we are going to use the opposite operation and subtract 6 from both sides so as to remove 6.

⟼ [tex] \tt{6 - 6 - 2x = 3 - 6}[/tex]

⟼ [tex] \tt{ - 2x = 3 - 6}[/tex]

Subtract 6 from 3 on the right.

⟼[tex] \tt{ - 2x = - 3}[/tex]

Now , we need to think about how to remove the coefficient -2 . Since the opposite of multiplication is division , we are going to divide both sides by -2.

⟼ [tex] \tt{ \frac{ - 2x}{ - 2} = \frac{ - 3}{ - 2}} [/tex]

⟼ [tex] { \tt{x = \frac{3}{2}}} [/tex]

[tex] \pink{ \boxed{ \boxed{ \underline{ \tt {Our \: final \: answer : \boxed{ \underline{ \tt{x = \frac{3}{2}}}}}}}}} [/tex]

Hope I helped ! ツ

Have a wonderful day / night ! ♡

▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁▁